Critical Analysis of the Synergy between Laboratory Technicians, Nurses, and Epidemiology Experts in Public Health Surveillance - Badawi , Majdi Adel; Alshehri , Mahayl Ahmed; Aldeen , Halah Abdulelah J; Almalawi, Ali Abdullah; Alghamdi , Majed Ali; Alshehri , Abdullah Salem A; Alqahtani , Hashem Saeed; alyami , Abdulhadi Hamad A; Lasloom , Saleh Hamad A; Lesloom , Ali Hadi A; Alherbi, Fahad Ruwaybih R; Alqahtani , Abdullah Mohammed; et al. (Journal of Ecohumanism, 2024)
An important technique in disease control, prevention, and surveillance of public health concerns involves a multidisciplinary healthcare team, including laboratory staff, nurses, and epidemiologists. All these roles play a part in data collection, analysis, and intervention strategies in what constitutes a highly synergistic and effective model for enhancing public health. This paper employs critical analysis to explain how laboratory technicians, nurses, and epidemiologists interactively function in the public health surveillance system. By looking at the functions of this teamwork, this paper evaluates the opportunities and risks of the different roles of these work partnerships. This synergy in task performance improves the functioning of the identification systems of disease threats, integrated with technology and constant staff training. The research also addresses challenges that could negatively affect the attainment of optimum collaboration: poor communication, issues of resources, and unavailability of standardized processes. Lastly, suggestions to enhance coordination between these healthcare professionals in public health surveillance systems worldwide are presented.